TEOLOGI GENDER, SEX, FENOMENA LGBTIQ DI BARAT DAN DI GEREJA-GEREJA DI INDONESIA DITINJAU DARI PERSPEKTIF REFORMED INJILI : . - Gatsper Anderius Lado (Sekolah Tinggi Teologi Excelsius, 2024)
Abstract: In the beginning God created man and ordained only two genders, male and female, and they could marry and have offspring (Genesis 2:18, 21-25). Humans created a new definition where there were genders that were not male and female, and then they also made a new understanding that men could marry men (homosexuals) and women could marry women. The purpose of this research is to analyze the Theology of Gender, Sex, LGBTIQ Phenomenon in the West and in Churches in Indonesia from the perspective of Reformed Evangelical. This study uses a descriptive qualitative research method. The result of this study is that the LGBTIQ phenomenon is understood in Evangelical Reformed theology as a deviation from divine design due to the fall of man in sin. The Church must uphold the Bible's teaching on gender and sexuality while showing love and pastoral support to LGBTIQ individuals